Pengaruh Disiplin Kerja, Motivasi dan Loyalitas Terhadap Kinerja Karyawan pada PT Majau Inti Jaya Cabang Berau - Khoirin Nida; Tuti Wediawati Noor (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Human resources are an important aspect in a small group, organization or company. Human resources must be managed properly to be able to create a good workforce to provide optimal results. Even though technology is currently developing very rapidly, it does not mean that it does not require human labor anymore, because the company's goals do not depend on technology but on quality human resources. This study aims to determine the effect of work discipline, motivation and loyalty on employee performance partially and simultaneously. This study uses a type of quantitative research through an associative approach with a Likert scale. The sampling technique used is purposive sampling technique with a sample of 105 respondents from PT Majau Inti Jaya employees. This study uses Statistical Package for the Social Science (SPSS Version 26) software to test the hypothesis. The results of this study indicate that there is a significant effect on motivation and loyalty while work discipline has no significant effect on employee performance. However, simultaneously the three variables have a significant influence on employee performance